DHA-rich fish oil increases the omega-3 index and lowers the oxygen cost of physiologically stressful cycling in trained individuals - Hingley, L.; Macartney, M. J.; Brown, M. A.; McLennan, P. L.; Peoples, G. E. (International Journal of Sport Nutrition and Exercise Metabolism, 2017)
Dietary fish oil, providing docosahexaenoic acid (DHA) modulates oxygen consumption and fatigue in animal models. However, in humans predominately supplemented with high eicosapentaenoic acid (EPA), there is no evidence of endurance performance enhancement. Therefore, this study examined if DHA-rich fish oil could improve repeated bouts of physiologically stressful cycling and a subsequent time trial in a state of fatigue. Twenty-six trained males took part in a double-blind study and were supplemented with either 2 × 1g/day soy oil, Control) or DHA-rich tuna fish oil (Nu-Mega) (FO) (560mg DHA / 140mg eicosapentaenoic acid (EPA), for 8 weeks. Maximal cycling power (3 × 6s), isometric quadriceps strength (MVC), Wingate cycling protocol (6 × 30s) and a 5min cycling time-trial were assessed at baseline and eight weeks. The Omega-3 Index was not different at baseline (Control: 4.2 ± 0.2; FO: 4.7 ± 0.2%) and increased in the FO group after eight weeks (Control: 3.9 ± 0.2; FO: 6.3 ± 0.3%, p < .01). There was no effect of DHA-rich fish oil on power output of maximal 6s cycle sprinting (Control: Pre 1100 ± 49 Post 1067 ± 51; FO: Pre 1070 ± 46 Post 1042 ± 46W), during 5min time trail (Control: Pre 267 ± 19 Post 278 ± 20; FO: Pre 253 ± 16 Post 265 ± 16 W) or maximal voluntary contraction force (Control: Pre 273 ± 19 Post 251 ± 19; FO: Pre 287 ± 17 Post 283 ± 16 Nm). Nevertheless, relative oxygen consumption was reduced the FO group during the cycling time trial (Control: -23 ± 26; FO: -154 ± 59ml O2/min/100W p < .05) suggesting improved economy of cycling. We conclude that DHA-rich fish oil, successful at elevating the Omega-3 Index, and reflective of skeletal muscle membrane incorporation, can modulate oxygen consumption during intense exercise.